An architectonics of desire: the person on the path to Nada in John of the Cross - F. England (Acta Theologica)
The strenuous ascetic that is established in The Ascent of Mount Carmel and The Dark Night by John of the Cross, frequently, and not illegitimately, is viewed as the purging of desire, but often to the extent that desire exclusively is perceived as a detrimental and negative quality. With a modest shift in perspective, this article attempts to read John through the lens of desire, rather than against it. It employs the notion of ‘desireless desire’, in order to describe John’s final position of waiting as one that neither dispenses with an authentically human and desiring subject, nor compromises the final aim of union with God.